EKSPLORASI PERAN LINGKUNGAN SOSIAL DAN POLA ASUH ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI - Cahya, Suci Ati; Siregar, Mhd. Fuad Zaini (CAHAYA: Journal of Research on Science Education, 2024)
This research explores how social environments and parenting contribute to early childhood character formation. Early childhood plays a crucial role in the formation of human beings, and factors such as family environment and parenting have a great impact on their social-emotional development. This study used qualitative research methods with a descriptive approach, with the research subjects consisting of three children aged 4-6 years and data collected from their parents. The results of the study showed that active parenting that is sensitive to children's emotional needs tends to result in positive behaviour. In addition, the study highlighted how these children may exhibit unique, sometimes unacceptable behaviours that are influenced by the family environment and parenting style. In conclusion, this study emphasises the importance of the role of parents in providing appropriate attention and supportive environments that promote positive character traits in growing children, as well as the need for understanding and appropriate intervention in this process.